Cell volume changes as revealed by fluorescence microscopy: Global vs local approaches - Awadová, Thuraya; Pivoňková, Helena; Heřmanová, Zuzana; Kirdajová, Denisa; Anděrová, Miroslava; Malínský, Jan (Journal of neuroscience methods, 2018)
BACKGROUND: Several techniques for cell volume measurement using fluorescence microscopy have been established to date. In this study, we compare the performance of three different approaches which allow for estimations of the cell volume changes in biological samples containing individual fluorescently labeled cells either in culture or in the tissue context. The specific requirements, limitations and advantages of individual approaches are discussed. NEW METHOD: Global morphometric data are quantitatively compared with local information about the overall cell volume, represented by the concentration of a mobile fluorophore accumulated within the monitored cell. RESULTS: Volume changes induced by variations in the extracellular osmolarity in murine fibroblasts and astrocytes either in the culture or in the acute brain slices were registered by the three- and two-dimensional morphometries and by local fluorescence intensity measurements. The performance of the latter approach was verified using FRAP assessment of the fluorophore mobility. Significantly lower amplitudes of the cortical astrocytes swelling were detected by three-dimensional morphometry, when compared to the other two approaches. Consequently, it failed to detect temperature-induced cell volume changes. COMPARISON WITH EXISTING METHOD(S): The three most popular methods of cell volume measurement are compared to each other in this study. CONCLUSIONS: We show that the effectivity of global morphometry-based volumetric approaches drops with the increasing cell shape complexity or in the tissue context. In contrast to this, the performance of local fluorescence intensity monitoring, which is also fully capable of reflecting the instant cell volume variations remains stable, independent of the system used and application.
Keywords: Animals; Cell volume changes; 3T3 Cells; Fluorescent Dyes; astrocyty; Microscopy, Fluorescence; Morphometry; zobrazování trojrozměrné; Imaging, Three-Dimensional; Fibroblasts; Hypertonic Solutions; Cell Size; hypotonické roztoky; Mice; hypertonické roztoky; fibroblasty; fluorescenční barviva; kultivované buňky; fluorescenční mikroskopie; myši; Astrocytes; Cells, Cultured; Hypotonic Solutions; Calcein; velikost buňky; Isotonic Solutions; isotonické roztoky; buňky 3T3; mozková kůra; Cerebral Cortex; zvířata; Microscopy, Confocal; konfokální mikroskopie; Fluorescence microscopy